The mode of endurance exercise influences changes in EEG resting-state graphs among high-level cross-country skiers - Büchel, D.; Torvik, P. Ø.; Lehmann, T.; Sandbakk, Ø.; Baumeister, J. (Medicine & Science in Sports & Exercise, 2023)
Purpose Acute bouts of exercise influence the communication and organization of brain networks, with exercise intensity and volume regarded as key moderators. However, differences in coordination demands and limb involvement between exercise modes may also affect the communication and organization of brain networks after exercise and should be considered additionally. This study aimed to investigate the effect of mode on exercise-induced changes in electroencephalogaphy (EEG) resting-state networks comparing running (RUN) and cross-country skating (XC).